Immature stages of the Zebra Hairstreak butterfly, Arawacus separata (Lepidoptera: Lycaenidae): a model organism for studies on mimicry and mutualism - Dresch, Flora; Lima, Luan Dias; Romanowski, Helena Piccoli; Kaminski, Lucas Augusto (Zootaxa, 2025)
Hairstreak butterflies are model organisms in evolutionary biology due to the variety of predator-avoidance strategies they possess, including false head mimicry and symbiosis with ants, both of which Zebra Hairstreaks employ. Natural history information is basic for the generation of hypothesis-driven research in ecology and evolution, especially for holometabolous organisms. Here, the complete life cycle of the Zebra Hairstreak Arawacus separata is described for the first time. The natural history records, including citizen science, for other Zebra Hairstreaks species in Eumaeini were also reviewed. Host plant records for A. separata indicate that its caterpillars are oligophagous on Solanaceae, being locally specialized on the shrub Cestrum strigilatum (Solanaceae). Development from egg to adult was found to last 30 days. Caterpillars underwent four instars with cryptic coloration and texture. The larval tegument is covered by short dendritic setae and pore cupola organs (PCOs), and, from the second instar on, shows a dorsal nectary organ (DNO). Caterpillars live on plants surrounded by ants throughout their entire ontogeny. Facultative symbiosis was observed in all instars with seven ant species in four genera. Myrmecophily is potentiated by honeydew-producing hemipterans and attractive sap of leaf lesions. Territory occupancy of males and non-aerial contests suggest a neglected role of sexual selection in the evolution of the false-head traits. Due to the typical false-head wing coloration pattern and myrmecophily, A. separata is proposed as a model organism to study mimicry and mutualism.